ANALISIS AREA PERLINDUNGAN SISTEM PROTEKSI PETIR PADA GEDUNG DENGAN SIMULASI PENEMPATAN DAN JUMLAH FINIAL - Seniari, Ni Made; Supriyatna, Supriyatna; Natsir, Abdul; Adnyani, Ida Ayu Sri; Ginarsa, I Made; Adha, Farhan; Eduarsa, Made Octa; Karni, Wais Al; Dharma S, Bagus Widhi (Universitas Mataram, 2024)
The theory and application of external lightning protection systems for buildings are not included in the curriculum of the Electrical Engineering Department. Instead, this material is introduced to students through skill training outside regular class schedules, with a focus on components of external lightning protection systems such as finials, down conductors, and grounding. The obligation to install lightning protection systems on buildings is mandated by Law No. 28 of 2002 and Government Regulation No. 36 of 2005. Protection from lightning requires precise planning to be effective in safeguarding buildings. Analysis of lightning strike phenomena and their consequences can be conducted by applying theoretical principles, such as electric fields, magnetic fields, induction voltage, and various theorems related to lightning strike phenomena. Students are provided with an understanding of the concept of lightning strikes, the potential dangers, and the damage they can cause to buildings, living beings, and electronic equipment both inside and outside the building that is affected by lightning strikes. In this simulation, each group is given images of buildings with varying roof shapes and sizes. The buildings are equipped with external lightning protection systems, including the number and placement of finials on the roof, which are then simulated. The effectiveness of the finials placed in these locations is tested to analyze the extent of protection, to ensure that the building is protected from the dangers of lightning strikes. A total of 40 students participated in this activity, divided into 8 groups. Five groups successfully simulated the installation of finials to achieve an effective level of protection against lightning strikes, while the remaining three groups could only determine the extent of the protection area without being able to plan the installation efficiently. This training provides a benefit by enhancing the knowledge and skills of the students. The students' enthusiasm is reflected in active discussions and question-and-answer sessions that contribute to problem-solving.